Optimization of Starter Concentration of Thermophilic Bacteria Consortium from Mudiak Sapan to Produce Biolectricity - Francantika, Manja; Irdawati, Irdawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The increasing problem of the electrical energy crisis encourages the need for efforts to develop environmentally friendly energy sources, for example, MFC. MFC using a consortium of thermophilic bacteria can provide advantages because it increases the reaction kinetics on the anode which contributes to the performance of the fuel cell. This study aims to optimize the concentration of thermophilic bacteria consortium as a starter in MFC. This study used thermophilic bacterial consortium MS 12 and MS 18 isolates from Mudik Sapan hot spring, and tested five different starter concentrations (3%, 6%, 9%, 12%, and 15%). The bacterial cultures were fermented in a two-chamber bioreactor of the MFC system with voltage measurements every 2 hours for 24 hours. Results showed the 9% concentration produced the highest average voltage output of 0.8043 V, indicating optimal electrogenic performance. This study highlights the important role of starter concentration in improving MFC efficiency.